2023
DOI: 10.3389/fimmu.2022.1094110
|View full text |Cite
|
Sign up to set email alerts
|

The lung, the niche, and the microbe: Exploring the lung microbiome in cancer and immunity

Abstract: The lung is a complex and unique organ system whose biology is strongly influenced by environmental exposure, oxygen abundance, connection to extrapulmonary systems via a dense capillary network, and an array of immune cells that reside in the tissue at steady state. The lung also harbors a low biomass community of commensal microorganisms that are dynamic during both health and disease with the capacity to modulate regulatory immune responses during diseases such as cancer. Lung cancer is the third most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…While these avenues are promising, it is essential to note that the development of metal-based drugs as therapies for microbiome modulation is in its nascent stages. Moreover, the link between microbiome modulation and cancer prevention remains a complex issue that requires more research [118,120,329,330]. While it is known that chronic inflammation can contribute to cancer development and that bacterial imbalances in the lungs can drive this inflammation, it is not yet entirely clear how effectively and consistently altering the microbiome can reduce cancer risk.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…While these avenues are promising, it is essential to note that the development of metal-based drugs as therapies for microbiome modulation is in its nascent stages. Moreover, the link between microbiome modulation and cancer prevention remains a complex issue that requires more research [118,120,329,330]. While it is known that chronic inflammation can contribute to cancer development and that bacterial imbalances in the lungs can drive this inflammation, it is not yet entirely clear how effectively and consistently altering the microbiome can reduce cancer risk.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…is a Gram-negative bacterium that has been previously associated with nosocomial infections, and some studies have suggested a potential link between pathogenic bacteria such as Acinetobacter spp. and lung cancer development or progression [27,28]. Further studies are needed to explore the potential role of Acinetobacter spp.…”
Section: Important Findingsmentioning
confidence: 99%
“…Although the emergence of immunotherapy has provided a chance of survival for patients with advanced disease, 60% of patients do not have immunotherapy driver genes, and even the immune response rate of patients with NSCLC is only 15-25% ( 2 ).In addition, some patients undergo immunotherapy for a certain period and develop immune escape, while others discontinue treatment due to severe immune-related adverse effects ( 3 ). If the disease is diagnosed early, the five-year survival rate of lung cancer patients can be increased to 59% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota is a community of all microbial species, including bacteria, fungi, viruses, archaea, and protozoa. Depending on their preferences for nourishment and oxygen, different microbes are often found on human body surfaces that come into touch with the external environment, including the skin, mouth, respiratory system, gastrointestinal tract, and urine tract ( 4 ). The human microbiota begins to colonize at birth.…”
Section: Introductionmentioning
confidence: 99%